Еuropean mechanism of protection of constitutional rights and freedoms of a person in the context of activity of OSCE - Толкачова, Ірина Анатоліївна; Полінська, Дар’я Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
Peculiarities of activity of OSCE are considered in the article. The role of OSCE in solving questions of protection of human rights and freedoms, security, strengthening of peace, stability and democracy is researched. According to Art. 3 of the Constitution of Ukraine the human being, his or her life and health, honour and dignity, inviolability and security are recognised in Ukraine as the highest social value. Human rights and freedoms and their guarantees determine the essence and orientation of the activity of our State. Since the Organization for Security and Cooperation in Europe (OSCE) is the largest international transatlantic intergovernmental regional organization in the world which solves the questions of security, strengthening of peace, stability and democracy, it is important to study peculiarities of its activity. OSCE includes fifty seven (57) member states (Decision of the Council of Ministers of OSCE № MC.DEC/2/12 dated November 21st, 2012 on joining of Mongolia to OSCE) and is an instrument of early prevention of conflicts, regulation of crises and post-conflict renewal, favours overcoming of discrepancies between states and forming of trust on the basis of cooperation. OSCE follows the concept of comprehensive security and carries out work in three directions: military and political, economical and environmental, and human. The Verkhovna Rada of Ukraine became member of the Parliamentary Assembly (PA) of OSCE according to succession on January 30th, 1992. The order of formation of Permanent Delegation of the Verkhovna Rada of Ukraine in PA OSCE is determined by the Regulations On Permanent Delegation of the Verkhovna Rada of Ukraine in the Parliamentary Assembly of the Organization for Security and Cooperation in Europe. Principles and standards in the sphere of human rights, adopted by the international community, establish supremacy of universal values over all others, have a considerable influence both on formation of national legislation as a whole, and on its separate institutes. Basic international documents in mentioned sphere became the incarnation of most progressive ideas, created by humanity during many centuries. There main guarantees of deserved human existence, protection of his or her rights and freedoms which are fixed in a juridical form in them.